2009 Loughborough Antennas &Amp; Propagation Conference 2009
DOI: 10.1109/lapc.2009.5352413
|View full text |Cite
|
Sign up to set email alerts
|

SAR analysis in human head model exposed to mobile base-station antenna for GSM-900 band

Abstract: Friis transmission equation combined with Finite Difference in Time Domain (FDTD) method has been used to carry out investigation on Specific Absorption Rate (SAR) inside the human head model exposed to a 100 Watt GSM Base Station Antenna (BSA) at GSM-900 band. Maximum local SAR (MLSAR) has been calculated at 925 MHz, keeping distance between head and BSA in the range of 0.5 m to 5.0 m. The human head is modelled as an inhomogeneous sphere of diameter 21.0 cm. The objective of this study is to estimate MLSAR i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…The specific absorption rate (SAR) of the antenna has also been calculated using full‐wave simulator. The human head has been modeled with a sphere of radius 7.5 cm with ε r = 51, μ r = 1 and σ = 1.5 S/m . The simulation result has been presented in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The specific absorption rate (SAR) of the antenna has also been calculated using full‐wave simulator. The human head has been modeled with a sphere of radius 7.5 cm with ε r = 51, μ r = 1 and σ = 1.5 S/m . The simulation result has been presented in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The number of cell towers is increasing rapidly, and electromagnetic (EM) waves emitted from the Base Station Antennas (BSAs) may have adverse effects on human beings or on other living animals [1][2][3][4][5]. It has also been reported that continuous exposure to microwave radiation from cell phone towers causes serious health problems over the years [6][7][8].…”
Section: Introductionmentioning
confidence: 99%